Signaling during engulfment: the beginnings of a good meal - Ravichandran, Kodi (Henry Stewart Talks, 2007)
Background on engulfment of apoptotic cells, Early lessons from the worm and graduating to mammals, GULP and LRP1 in engulfment, Role of ELMO and Dock180 proteins in engulfment, The mechanisms leading to Rac activation and regulation of the cytoskeleton during engulfment
Archived at 2021/02/25